Complement C4 induces regulatory T cells differentiation through dendritic cell in systemic lupus erythematosus. Issue 1 (December 2015) - Cheng, Hong-Bin; Chen, Rong-Yi; Wu, Jing-Ping; Chen, Li; Liang, Yan-Hua; Pan, Hai-Feng; Pan, Zi-Feng; Zhang, Qing-Hua; Li, Qing; Du, Tian-Xi; Lv, Yong-Mei; Shi, Jian-Qiang
Abstract Background Systemic lupus erythematosus (SLE) is a prototypic systemic autoimmune disease. Complement component 4 (C4) has be proved to play a role in pathogenesis of SLE. In the present study, we investigated the effect of C4 on T cells differentiation. Methods Thirty SLE patients were included in this study. CD4+ T cells were isolated from healthy subjects, and dendritic cells (DCs) were isolated from healthy subjects or SLE patients. C4 was supplemented to co-incubate with T cells and DCs. Results Serum C4 concentration was positively correlated with regulatory T cell (Treg) percentage (R2  = 0.5907, p < 0.001) and TGFβ concentration (R2  = 0.5641, p < 0.001) in SLE patients. Different concentrations of C4 had no effect on T cells differentiation. Co-incubated T cells with DCs and C4 for 7 days, the Treg percentage and TGF-β concentration were significantly elevated. In addition, pre-treated DCs (from healthy subjects or SLE patients) with C4 and then co-incubated with T cells, the increases of Treg percentage and TGF-β concentration were also observed. Conclusion C4 takes part in T cells differentiation to Treg cells via DCs.